DGAM METHODOLOGY TO DESIGN A KNOWLEDGE MANAGEMENT SYSTEM - Calva, Bernardo; Machorro, Angel; Gurruchaga, Eloisa (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
The “Subdirección de Ingeniería y Desarrollo de Obras Estratégicas” of “Petróleos Mexicanos” determined that it was necessary to accelerate the evolution of knowledge within this organization, in order to achieve this purpose the “Subdirección de Ingeniería y Desarrollo de Obras Estratégicas” decided to develop and implement a Knowledge Management System. However, when trying to implement a Knowledge Management System, it was found that knowledge management models only provide generic sets of steps on how to carry out Knowledge Management, without specifying how to develop and implement Knowledge Management Systems in any organizations; hence the need of developing a Methodology that may suit the specific purposes required by the “Subdirección de Ingeniería y Desarrollo de Obras Estratégicas”, this four stages Methodology of Knowledge Management, is denominated DGAM. This nomination corresponds to each one of the four stages of the methodology: Determination, Generation, Accessibility and Maintenance.